A.A.V.V., El Gran Capitán, de Córdoba a Italia al servicio del Rey. Córdoba, CajaSur, 2003. 425 págs., ISBN 84-7959-520-5. - Greco, Enrique (2005)
Fil: Greco, Enrique. Investigador independiente; Argentina